Low power modulator for capsule endoscope - Lioe, De Xing (2013)
The evolution of wireless communication and circuit integration has brought medical science and devices to a new dimension. This leads to the invention of wireless capsule endoscope. Conventional endoscope for gastrointestinal diseases diagnoses which are uncomfortable for patients, have certain limitations in performing diagnosis or treatment. Thus it is not feasible for the conventional endoscope, in terms of travelling through a long and convoluted small intestine. Wireless capsule endoscopy addresses the disadvantages of the conventional wired endoscopes where it can reach the small intestine and achieve diagnosis without discomforting the patients as well as easily travel through the digestion tract. Being a wireless device, the design of the capsule endoscope transmitter is paramount for the overall performance. Power consumption is the utmost important aspect in the consideration. The selection of the standard or carrier frequency is optimum to ot requirements which are image quality and frame rate. Considering the loss against frequency in a human body wireless communication, Industrial, Scientific, Medical (ISM) band of 434 MHz is employed in the design of the transmitter. This band has lower loss and relatively higher data rate compared to other standards. Inductorless architecture was adopted in the circuit design to reduce the circuit area, thus contribute to the reduction of capsule size. Taking into account on the aspects in concern, the up-conversion mixer, ring oscillator and the integrated modulator is designed using CMOS 0.13 μm technology with voltage supply of 1.2 V. Low power consumption is achieved where the mixer consumes only 594 uA, which is equivalent to 712.8 uW of power consumption. Positive linearity is achieved with Third-Order Intercept Point (IIP3) of 2 dBm, while the dynamic range which is represented by P1dB is -5.43 dBm. Noise figure of the mixer is found to be 23 dB. The ring oscillator consumes 740 μA which translate to 888 μW of power consumption. Phase noise achieved is -81 dBc/Hz at 160 kHz of offset frequency. The integrated modulator achieves power consumption of 1.88 mW,which is superior compared to other reported work. Battery life utilizing the proposed architecture can reach 13.8 hours compared to the average of 8 hours operational time. Die area utilized is merely 0.44 mm2 which allows better integration of other blocks in the capsule endoscope.